Microbiological Characteristics of the Unrecorded Wild Yeasts from Jeju Island and Jangsado in Southern Coast, Korea - Jeong-Su Moon; Hyang Burm Lee; Jong-Soo Lee (한국균학회지)
The present study aimed to screen unrecorded wild yeasts from Jeju lsland and Jangsado on the southern coast of Korea, and to investigate their microbiological characteristics. To date, Coniozyma leucospermi JJD37-2, Hanseniaspora thailandica JJD44-1, Kluyveromyces nonfermentans JJD15-1, Kockovaella fuzhouensis JJD47-3, Vishniacozyma heimaeyensis JJD8-4, Candida carpophila JSDH24-1, Wickerhamomyces strasburgensis JSDH34-2, Candida savonica HJD6-4, and Candida karawaiewii YP23-3 have not been previously recorded in Korea. In the present study, we investigated the microbiological characteristics of these previously unrecorded yeasts. Except for W. strasburgensis JSDH34-2 strain, none of the strains formed spores, and only the C. leucospermi JJD37-2 strain formed pseudomycelia. Almost all strains grew well in yeast extract-peptone-dextrose (YPD) medium, potato dextrose (PD) medium and yeast extract-malt extract (YM) media. C. carpophila JSDH24-1 and W. strasburgensis JSDH34-2 also grew well in YPD medium containing 10% NaCl. H. thailandica JJD44-1 is fermented to produce glucose, fructose and mannose.